Cultural adaptation between western buyers and chinese suppliers - Jia, Fu (Cranfield University, 2009)
There are undoubtedly multiple factors that may contribute to the failure of a relationship, such as product quality or supplier reliability; however, when Western buyers source from China and attempt to build partnerships with Chinese suppliers, it is highly likely that they and their Chinese partners will encounter relational difficulties rooted in cultural differences between China and the West. Cultural adaptation is proposed as a solution to this problem; however the process of how each partner in a China-West partnership adapts to each other over time is not clear. Furthermore, the causal relationship between cultural adaptation and the mutual benefits of partnership has not previously been tested, nor have the contextual factors influencing the cultural adaptation process been identified. A multiple case study method was selected to answer three research questions developed from the three gaps identified above. Four China-US/UK cross cultural partnerships were selected for case analysis, which involved the retrospective evaluation of how both parties in each partnership adapt. The main instrument of data collection was the semi-structured interview supplemented with questionnaires and observations. The research concludes that as a result of cultural adaptation by both parties, a hybrid culture forms at the interface between Western buyers and their Chinese suppliers and is a combination of Guanxi and Western rules and procedures. Organizations as a whole do not adapt culturally, but rather those individuals working closely with each other at the interface of the two organizations including those working for Western buyer IPOs (International Purchasing Offices) in China and those who are top or middle level management in the Chinese suppliers. Two emerging contextual variables including the ownership of Chinese suppliers and the structure of IPOs have been identified from cross case analysis. The research also concludes that the higher the level of cultural adaptation the greater the mutual benefits perceived by both parties of the relationship.